Research progress of aqueous Zn–CO2 battery: design principle and development strategy of a multifunctional catalyst - Guo, Wenqi; Wang, Yukun; Yi, Qun; Devid, Edwin; Li, Xuelian; Lei, Puying; Shan, Wenlan; Qi, Kai; Shi, Lijuan; Gao, Lili (Frontiers in Energy Research, 2023)
Aqueous Zn–CO2 battery possesses a large theoretical capacity of 820 mAh g-1 (5855 mAh cm-3) and high safety, showing a unique position in carbon neutrality and/or reduction and energy conversion and storage, which has developed rapidly in recent years. However, obstacles such as low value-added products, low current density, high overvoltage, and finite cycles impede its practical application. Cathode catalysts, as a key component, have a significant influence on gas cell performance. Despite many updated papers on cathode materials for aqueous Zn–CO2 batteries, a systematic summary has rarely been reported, and even less is mentioned about the design principle and development strategy for efficient catalysts. Relying on the structure and mechanism of the Zn–CO2 battery, this review discusses the research progress and existing challenges, and, more importantly, the design strategies and preparation methods of the efficient cathode are proposed, centering on material structure, charge distribution, and coordination environment. Finally, in this review, the opportunities for the development of a high-performance Zn–CO2 battery are highlighted, which enables enlightening the future exploration of next-generation energy storage systems.